ANALISIS PERTUMBUHAN TANAMAN BAWANG MERAH (Allium cepa L. Kelompok Aggregatum)VARIETAS LEMBAH PALU YANG DIBERIKAN ATONIK SERTA PUPUK ORGANIK CAIR - Hendra Hendra; Sakka Samuddin; Muhammad Anshar (Universitas Tadulako, 2016)
This study aimed to of analyze the growth of Lembah Palu shallot variety (Allium cepa L. Aggregatum group). This study took place in February-May 2015 and conducted in Bulupountu village, Sigi district of Central Sulawesi Province. This study used a randomized complete block design (RCBK) within which treatments were grouped based on the diameter of shallot bulbs. The treatments consisted of five different atonic and liquid organic fertilizer (LOF) concentrations with four replicates. The treatments included control (A0), 5 ml atonic/l water (A1),40 ml LOF/l water (A2), 2.5 ml atonic/l water + 40 ml LOF/l water (A3), and 5 ml atonic/l water + 20 ml LOF/l water (A4). Data was analyzed using analysis of variance (ANOVA) and Honestly Significant Difference at 0.05 level. The treatments significantly affect total dry weight of crop, net assimilation rate,crop growth rate and leaf area ratio but total leaf area per plant not significant. Key Words : Atonic, liquid organic fertilizer, and Lembah Palu shallot variety.